Psychometric properties and convergent and predictive validity of an executive function test battery for two-year-olds - Mulder, Hanna; Hoofs, Huub; Verhagen, Josje; van der Veen, Ineke; Leseman, Paul P. M. (Frontiers in Psychology, 2014)
Executive function (EF) is an important predictor of numerous developmental outcomes, such as academic achievement and behavioral adjustment. Although a plethora of measurement instruments exists to assess executive function in children, only few of these are suitable for toddlers, and even fewer have undergone psychometric evaluation. The present study evaluates the psychometric properties and validity of an assessment battery for measuring EF in two-year-olds. A sample of 2437 children were administered the assessment battery at a mean age of 2;4 years (SD = 0;3 years) in a large-scale field study. Measures of both hot EF (snack and gift delay tasks) and cool EF (six boxes, memory for location, and visual search task) were included. Confirmatory Factor Analyses showed that a two-factor hot and cool EF model fitted the data better than a one-factor model. Measurement invariance was supported across groups differing in age, gender, socioeconomic status (SES), home language, and test setting. Criterion and convergent validity were evaluated by examining relationships between EF and age, gender, SES, home language, and parent and teacher reports of children’s attention and inhibitory control. Predictive validity of the test battery was investigated by regressing children’s pre-academic skills and behavioral problems at age three on the latent hot and cool EF factors at age two years. The test battery showed satisfactory psychometric quality and criterion, convergent, and predictive validity. Whereas cool EF predicted both pre-academic skills and behavior problems one year later, hot EF predicted behavior problems only. These results show that EF can be assessed with psychometrically sound instruments in children as young as two years, and that EF tasks can be reliably applied in large scale field research. The current instruments offer new opportunities for investigating EF in early childhood, and for evaluating interventions targeted at improving EF from a young age.